Spin Wave Modes in a Cylindrical Nanowire in Crossover of Dipolar-Exchange Regime - Justyna Rychły; Vera S. Tkachenko; Jarosław W. Kłos; Andriy N. Kuchko; Maciej Krawczyk (Proceedings, 2019)
Although the magnetic wires have been [1] broadly investigated, some of their dynamical properties, like: (anti)crossing between the spin wave modes and the impact of the magnetic field on the spin wave spectrum, still need to be explored. [...]